Prospek Konseling Komunitas bagi Individu Eks-Pecandu Narkoba (Studi Pada Lembaga Pasca-Rehabilitasi Narkoba Di Kota Semarang) - Haryadi, Rudi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Despite being free from addiction, ex-drug addicts clients are by no means free from problems at all. The potential for recurrence is still a scourge to watch out for. In this case the counselor faces new challenges to be able to provide services to this population. While post-rehabilitation institutions have been popping up in big cities, one of them is Semarang. This study aims to analyze the implementation of services in post-rehabilitation institutions in the city of Semarang, and assess how the prospects of community counseling if implemented in this institution. The case study was conducted at two post-rehabilitation institutions in Semarang City. Data collection techniques used by researchers are observation, interview, documentation study, and spreading of SOAR based questionnaire. The results found that there are similarities in the implementation of post-rehabilitation programs with a comprehensive counseling framework, but they have some drawbacks due to the lack of professional qualifications and empirical theoretical studies in them. The researcher then recommends the counselor to carry out appropriate standards-based community counseling on clients of drug addicts by taking into account all the resources, aspirations, opportunities, and expected performance.